Web Application Development for Syari Online Shop Using 4D Model Development - Yose Indarta; Ranuharja, Fadhli; Sukardi, Sukardi; Samala, Agariadne Dwinggo Samala; Ika Parma Dewi (Politeknik Ganesha Medan, 2022)
: Haransaf shop is a shop that sells clothes and all Muslim/Muslim knick-knacks. Depending results of observations and data searches directly to the field with increasing requests. The use of technology in data processing of Haransaf Online Store Transactions has not been effective and efficient so that reporting takes a long time. The recording of the Haransaf store report still uses a manual system, which is still written on notes and then recorded in the sales book. The focus of this research is on an attractive interface, ease of use, and delivery of product information to consumers by utilizing the website as an online service. The research method uses 4-D. The model in the development of an online store must use a 4D model. The 4D model has four stages, namely Define, Design, Develop and Disseminate. The website-based Haransaf Online Store that uses the Codeigniter 4 Framework, functions well to produce a sales management system that manages the Haransaf online store. With the existence of this online store, it is hoped that it can provide an increase in revenue at the Haransaf Store and benefits in the form of a wider scope.